DEVELOPMENT OF IDEAS OF THE SUBJECT-MATTER OF A MAN AND A WOMAN IN ANCIENT PHILOSOPHY - O. Yu. Shibarshina (Научный вестник МГТУ ГА)
In the article concepts of ancient philosophy of the classical period, and also philosophy of the Hellenistic schools in which the problem of regulation of the relations between the man and the woman was considered are analyzed. The features of formation of the gender relations in antique society are defined, conditions of emergence of the concept "social gender" are opened. A valid conclusion that in the period of Antiquity in the system of the gender relations the androtsentrizm dominated, priority value belonged to the man.